Selfies, #me: Glimpses of Authenticity in the Narcissus’ Pool of the Networked Amateur Self-Portrait - Donnachie, Karen Ann (2015)
This research addresses the ‘Selfie’ as a significant phenomenon of contemporary photography, its unique methods of production and distribution, as well as the possible motivations driving this particular genre of the (amateur) self-portrait. I will argue that the Selfie happens at the crossroads between performance, narcissism, social tick, an intrinsic desire for self-projection and a possibly irrational quest for authenticity in the contemporary photographic image, and that its ubiquity cannot help but change the idea of the photograph as we know it.